THE STRUGGLE FOR BATIK IDENTITY AS A GLOBAL INDONESIAN CULTURAL HERITAGE - Mauliska, Nur (Universitas Islam Zainul Hasan Genggong, 2024)
This article explores the struggle for batik identity as a global Indonesian cultural heritage, focusing on its international recognition and the challenges of preservation. The introduction outlines the importance of batik as a cultural symbol and the challenges faced in the context of globalization. The research method employs a literature study approach, including an analysis of books, reputable journals, and sources indexed in Web of Science and Scopus, to evaluate the role of batik in cultural identity and the impact of globalization on its preservation. The research findings indicate that the recognition of batik as a Masterpiece of Oral and Intangible Heritage of Humanity by UNESCO in 2009 has increased global awareness and strengthened batik's position in the international market. However, globalization has also posed challenges, such as competition with modern textile products and shifting preferences among the younger generation. The discussion highlights the need for innovation in design and marketing, as well as preservation efforts through government policies and community participation. Thus, to ensure the sustainability of batik as a cultural heritage, collaboration between the government, society, and creative industry players is necessary, along with continuous education to enhance interest and relevance of batik in the modern era.